The potential of using microalgae for simultaneous oil removal in wastewater and lipid production - Choong, Y.J. (Springer, 2020)
Abstract: Microalgae have received considerable attention in recent years due to their significant potential in contaminants removal from wastewater and can be used as a sustainable feedstock for biofuel production. However, existing researches on microalgae are mainly focused on inorganic nutrients (i.e., nitrogen and phosphorus) removal, while oil as one of the major pollutant classes has been lack of study. Therefore, the present work was aimed to use microalgae to remove oil in wastewater and for simultaneous lipid production. In this study, variables such as ozone flowrate, oil concentration, amount of microalgae seeds and cultivation pH value were introduced to optimize the oil removal efficiency and lipid yield. The optimized parameters that resulted the highest oil removal percentage (41.56) were as follows: 0.4 L/min of ozone flowrate, 3Â mL/L of oil concentration, 200Â mL/L of microalgae seeds and cultivation pH value of 3 to 5. Under this condition, the lipid content embedded within the microalgae cells was 41.5 and mainly consisted of unsaturated fatty acids. The present results affirmed the capability of microalgae to remove oil from wastewater and could produce higher lipid yield from the metabolized oil. Graphic abstract: Figure not available: see fulltext.. Â© 2020, Islamic Azad University (IAU).